Democrazia, partecipazione e conflitto: el caliente otoño latinoamericano - Lucia Picarella (Culture e Studi del Sociale)
This article analyzes, with a qualitative methodology, the problems underlying the delicate correlation between representation, participation, conflict, assessed in the context of the radical democracy studies and in consideration of the Latin American scenario, the laboratory par excellence of participatory practices, involved during the course of the last year by interesting protests and demonstrations. The outbreak of social conflict in this region has underlined the crisis and dysfunctionality of the democratic circuit, highlighting however interesting news compared to the past, both in terms of the peculiarity of the protest and its channeling for the purpose of redefining the political-institutional space, as well as incidence of digital ecosystems for the organization and maintenance of the action.